Psychology of sustainability an applied perspective - Jones, Robert G. (Robert Gordon) 1955- (Routledge, 2015)
"Psychology of Sustainability: An Applied Perspective examines the many psychological factors that lead to human behavioral effects on the environment. Because applied psychology is concerned with defining criteria and finding precursor variables that can be manipulated, this textbook is neatly structured to represent the principles of applied psychology. Each chapter will apply elements from a basic research area into the context of criteria specific to sustainability. Until recently, applied psychology received minimal attention from professors and professionals in sustainability. At the same time, increased interest has led many universities to offer courses on "Psychology of Sustainability." This book is the perfect text to provide an introduction to the subject. Throughout the book, readers will find new ways of framing questions related to human adaptability and evolutionary psychology. Psychology of Sustainability is ideal for students or professionals who are looking to contribute to the conversation"--